2015
DOI: 10.1111/tri.12612
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abdominal aortic calcifications in older living renal donors and its effect on graft function and histology

Abstract: SummaryWe assessed the prevalence of abdominal aortic calcification (AAC) in older living kidney donors and its effect on recipient eGFR and graft histology. A total of 292 consecutive living pairs with donor age ≥50 from 2003 to 2013 were identified (mean age 56; range 50-78; F/M: 1.8). Donor AAC was determined by prenephrectomy unenhanced CT. Recipient eGFR and spot urine protein: creatinine ratios (UPCRs) were recorded. A total of 180 recipients had 6-month protocol biopsies. AAC was present in 40.7% of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our findings suggest that, in some instances, factors leading to ESRD may exist in the allograft before donation, as may be the case with genetically determined kidney disease. By extension, our findings also suggest that asymptomatic (and subtle), early-stage lesions may exist in the allograft before donation, as has been found at implantation biopsy (29)(30)(31)(32)(33)(34)(35), and that these lesions might be clinically relevant.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings suggest that, in some instances, factors leading to ESRD may exist in the allograft before donation, as may be the case with genetically determined kidney disease. By extension, our findings also suggest that asymptomatic (and subtle), early-stage lesions may exist in the allograft before donation, as has been found at implantation biopsy (29)(30)(31)(32)(33)(34)(35), and that these lesions might be clinically relevant.…”
Section: Discussionsupporting
confidence: 78%
“…As in previous studies, histologic findings from T0 biopsies did not predict recipient renal function . However, in combination, the cited studies only included 17 hypertensive donors.…”
Section: Discussionmentioning
confidence: 86%
“…Aortic stiffness of living donors may also contribute to the recipient outcome beyond other parameters [ 41 ]. Another report also demonstrated that allografts from donors with vascular calcification had a high percentage of vascular fibrous intimal thickening and arteriolar hyaline thickening in the six-month surveillance biopsy [ 42 ]. The present study revealed that a higher ACI was associated with higher ci, ct, and ah scores.…”
Section: Discussionmentioning
confidence: 99%